The Relationship of Work Stress And Self-Control With Nurses' Performance In Providing Services At UOBF Nguling Health Center - Siti Muthmainnah; Nafolion Nur rahmat; Kurniawan Erman Wicaksono (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Introduction: Nurses are the most dominant health workers who provide 24-hour services, so they are vulnerable to work stress and require good self-control. This study aims to analyze the relationship between work stress and self-control with the performance of nurses in providing services at the UOBF Nguling Health Center. Method: The research study was a correlational analytical approach cross-sectional. The research sample was all nurses at the UOBF Nguling Health Center, with 31 nurses using the Total Sampling technique. The instruments used were work stress questionnaires and self-control with nurse performance. The research data were analyzed using the Spearman Rank Test. Results: The results of the research show that the p-value = 0.000 with a significance level of α = 0.05 (p <α = 0.05), so it can be concluded that there is a relationship between self-control with the performance of nurses in providing services at the UOBF Health Nguling Community Health Center. Work stress causes a decrease in performance or workability and poor work results or a decrease in nurse productivity. Conclusion: Self self-control in nurses, they can develop good behavior, be more responsible, be useful for themselves, patients, and others, and establish good relationships with patients and other people. Nurses must be able to improve their self-control abilities through modifying the environment to be responsive to support the provision of good nursing care.